2017
DOI: 10.1128/genomea.00116-17
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Two Naphthalene-Degrading Strains of Pseudomonas balearica, Isolated from Polluted Marine Sediment and from an Oil Refinery Site

Abstract: The genome sequences of Pseudomonas balearica strains LS401 (CCUG 66666) and st101 (CCUG 66667) have been determined. The strains were isolated as naphthalene degraders from polluted marine sediment and from a sample from an oil refinery site, respectively. These genomes provide essential data about the biodegradation capabilities and the ecological implications of P. balearica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Moreover, the genome sequences of two strains (S. balearica DSM 6083 T and strain LS401), which harbor the catechol meta-cleavage pathway, codified all components for channeling naphthalene into catechol (Figure 6), and both strains were able to grow using naphthalene and salicylate as sole carbon and energy sources (Table 1), which is in agreement with a previous study (Rossello et al, 1991). S. balearica strain CCUG 66667 (= st101), despite being originally described as naphthalene degrader (Dutta, 2001), was not able to grow on naphthalene as a sole carbon and energy source and no genes for naphthalene degradation were detected in its genome sequence, as previously reported (Salvà-Serra et al, 2017). This suggests that S. balearica strain st101 may have lost the naphthalene degradation capacity, which could be related to mobile genetic elements, such as plasmids, transposons, or integrative conjugative elements, being unstable in the absence of selective pressure (Phale et al, 2019).…”
Section: Degradation Of Aromatic Compounds By Stutzerimonas Balearicasupporting
confidence: 91%
“…Moreover, the genome sequences of two strains (S. balearica DSM 6083 T and strain LS401), which harbor the catechol meta-cleavage pathway, codified all components for channeling naphthalene into catechol (Figure 6), and both strains were able to grow using naphthalene and salicylate as sole carbon and energy sources (Table 1), which is in agreement with a previous study (Rossello et al, 1991). S. balearica strain CCUG 66667 (= st101), despite being originally described as naphthalene degrader (Dutta, 2001), was not able to grow on naphthalene as a sole carbon and energy source and no genes for naphthalene degradation were detected in its genome sequence, as previously reported (Salvà-Serra et al, 2017). This suggests that S. balearica strain st101 may have lost the naphthalene degradation capacity, which could be related to mobile genetic elements, such as plasmids, transposons, or integrative conjugative elements, being unstable in the absence of selective pressure (Phale et al, 2019).…”
Section: Degradation Of Aromatic Compounds By Stutzerimonas Balearicasupporting
confidence: 91%
“…We identified specific microbes that can be used as sensitive indicators of aquaculture impacts. These included P. balearica ( Figure 4 ), which has been associated with other contaminated wetland systems, suggesting that this taxon could be a potential bio-indicator of a disturbed mangrove ecosystem ( Salvà-Serra et al., 2017 ). Similar studies have also identified aquaculture effluent as a source of pathogens to the coastal ecosystem ( Garren et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 6,470scaffolds were produced for Sample C with an N50 of 24,471 bp and highest scaffold length 197,135 bp. Metassembler has been widely used to develop meta-genome assemblies [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] . The genome size of Sample C was 76.95Mb compared to 72.16Mb for Sample B.…”
Section: Discussionmentioning
confidence: 99%